2020
DOI: 10.1038/s41467-020-14860-6
|View full text |Cite
|
Sign up to set email alerts
|

Understanding solvent effects on adsorption and protonation in porous catalysts

Abstract: Solvent selection is a pressing challenge in developing efficient and selective liquid phase catalytic processes, as predictive understanding of the solvent effect remains lacking. In this work, an attenuated total reflection infrared spectroscopy technique is developed to quantitatively measure adsorption isotherms on porous materials in solvent and decouple the thermodynamic contributions of van der Waals interactions within zeolite pore walls from those of pore-phase proton transfer. While both the pore dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 86 publications
1
80
0
Order By: Relevance
“…68 Equilibrium constants to protonate pyridine (293 K) within zeolites differ when their pores are lled by solvents of different polarity, also highlighting the important role of proton-solvent complex stability. 69 Other studies of co-solvents within zeolites, based on IR spectra and gas-phase isopropanol dehydration probe reactions, suggest that the protic nature of solvents (e.g., acetic acid) and co-existing cations (e.g., Na + ) can change the type, number, and strength of Brønsted acid sites in zeolites. [70][71][72] Bridging the gap in mechanistic understanding from that of molecular species and complexes prevalent during gas-phase studies at H 2 O pressures well below saturation, to those of extended solvent networks and condensed phases around active sites that prevail during liquid-phase studies, requires considering how the clustered nature of alcohol-water intermediates at active sites evolves with the structure of solvating water networks conned within the same pores.…”
Section: Introductionmentioning
confidence: 99%
“…68 Equilibrium constants to protonate pyridine (293 K) within zeolites differ when their pores are lled by solvents of different polarity, also highlighting the important role of proton-solvent complex stability. 69 Other studies of co-solvents within zeolites, based on IR spectra and gas-phase isopropanol dehydration probe reactions, suggest that the protic nature of solvents (e.g., acetic acid) and co-existing cations (e.g., Na + ) can change the type, number, and strength of Brønsted acid sites in zeolites. [70][71][72] Bridging the gap in mechanistic understanding from that of molecular species and complexes prevalent during gas-phase studies at H 2 O pressures well below saturation, to those of extended solvent networks and condensed phases around active sites that prevail during liquid-phase studies, requires considering how the clustered nature of alcohol-water intermediates at active sites evolves with the structure of solvating water networks conned within the same pores.…”
Section: Introductionmentioning
confidence: 99%
“…Decades of work have shown that HBs among aqueous solvents and polar surfaces can affect the adsorption of alcohols within microporous solids, [8][9][10][11][12][13][14] transport of H 2 O through carbon nanotubes, [15][16][17] and the stability of reactive surface intermediates within zeolites. 5,6,[18][19][20][21] The role of confined water in biocatalysis, however, is more clearly understood due to the successful characterization of water structures within the catalytic clefts of enzymes. [22][23][24] This insight provided opportunities to design optimal solvents and mutations that improve enzymatic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Born-Haber thermochemical cycles provide a conceptual framework to deconstruct an apparent change in free energy between two states into individual contributions from distinct chemical processes. 18,21,60 Scheme 1 shows a series of chemical steps that conveniently deconvolutes measured values of ∆ ‡ into specific chemical interactions within Ti-zeolites that possess low (Scheme 1a) or high (Scheme 1b) densities of (SiOH) x . In this sequence, fluid-phase alkene molecules enter the pores of the Tizeolite, displace solvent molecules, and interact with the surrounding pore walls, which corresponds to a free energy of adsorption (∆ ) that depends primarily on the characteristic size of the surrounding pores.…”
Section: Influence Of H 2 O Structure and Reorganization On Liquid-phase Epoxidation Catalysismentioning
confidence: 99%
“…Decades of work have shown that HBs among aqueous solvents and polar surfaces can affect the adsorption of alcohols within microporous solids, [8][9][10][11][12][13][14] transport of H 2 O through carbon nanotubes, [15][16][17] and the stability of reactive surface intermediates within zeolites. 5,6,[18][19][20][21] The role of confined water in biocatalysis, however, is more clearly understood due to the successful characterization of water structures within the catalytic clefts of enzymes. [22][23][24] This insight provided opportunities to design optimal solvents and mutations that improve enzymatic performance.…”
Section: Introductionmentioning
confidence: 99%